Spider Veins Treatment using 1064 nm Long-Pulse Nd:YAG Laser - Ali, Mardukh S.; Awazli, Lutfi G.; Issa, Najim Abid (Iraqi Journal of Laser, 2020)
spider veins are clusters of Ectatic venules & are common finding on the lower limbs generally believed to be caused by multiple factors, including genetic predisposition, hormonal factors, gravity, occupation, pregnancy, becoming increasingly apparent with age, and trauma. Therapeutic options include sclerotherapy, surgical procedures, and treatment with different laser systems. Objectives: The purpose of the study was to evaluate the efficacy and safety of long pulsed (Nd:YAG) laser emitting at 1064nm in the treatment of spider veins. Patients, Materials and Methods: This prospective study was done in the laser medicine research clinics of the Institute of laser for postgraduate Studies / University of Baghdad from September 2016 until the end of December 2016. The study included ten patients between the ages of 22 to 55 years suffered from spider veins of the lower limbs. They were treated with a long pulsed (Nd:YAG) laser in a non contact technique using the following laser parameters (wavelength 1064 nm ,energy 30-73 J, pulse duration 10-30 ms, frequency 2Hz, spot diameter 3-7mm ). Laser therapy was performed on day zero and day fourteen. Clinical assessments were carried out before laser therapy and immediately after the first laser therapy, 2 weeks, 4 weeks, and 6 weeks later. Results: Results showed that there was a remarkable improvement for all patients after the second treatment. Six patients (60%) showed a complete disappearance of the spider veins and there was an improvement for four patients (40%) with no significant intraoperative and postoperative pain or complications, within short operative time. Conclusion: The long pulsed (Nd:YAG) laser (1064 nm) is an effective and safe treatment option for lower limbs spider veins